2006
DOI: 10.1037/0735-7044.120.4.842
|View full text |Cite
|
Sign up to set email alerts
|

Chronic stress impairs spatial memory and motivation for reward without disrupting motor ability and motivation to explore.

Abstract: This study uses an operant, behavioral model to assess the daily changes in the decay rate of shortterm memory, motivation, and motor ability in rats exposed to chronic restraint. Restraint decreased reward-related motivation by 50% without altering memory decay rate or motor ability. Moreover, chronic restraint impaired hippocampal-dependent spatial memory on the Y maze (4-hr delay) and produced CA3 dendritic retraction without altering hippocampal-independent maze navigation (1-min delay) or locomotion. Thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
112
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 154 publications
(126 citation statements)
references
References 60 publications
6
112
2
2
Order By: Relevance
“…While the 6h/21d group may have had less access to food compared to the other groups, we have previously shown that chronically stressed rats that are food restricted actually consume more food to maintain their weights than control rats (Kleen et al, 2006). Additional evidence illustrating that stress-induced weight loss is not dependent upon food access is shown in studies using the stress hormone, corticosterone.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…While the 6h/21d group may have had less access to food compared to the other groups, we have previously shown that chronically stressed rats that are food restricted actually consume more food to maintain their weights than control rats (Kleen et al, 2006). Additional evidence illustrating that stress-induced weight loss is not dependent upon food access is shown in studies using the stress hormone, corticosterone.…”
Section: Discussionmentioning
confidence: 55%
“…While some reports demonstrate that chronic stress impairs motivation (Mizoguchi et al, 2002), including studies using chronic restraint for 6h/21d (Kleen et al, 2006), most chronically stressed rats tested on the Y-maze show motivation to explore (Conrad et al, 1996;Wright and Conrad, 2005;Wright et al, 2006). One of the advantages of using the Ymaze is that motivation is dependent on a rat's innate interest in novelty seeking, and food restriction is not needed to motivate rats to perform (for review see Conrad, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations